Design and practice of gamified basketball teaching model based on edge computing: Exploration of improving middle school students’ participation and learning outcomes - Liu, Yu; Narmluk, Mongkhon (Edelweiss Applied Science and Technology, 2025)
Leveraging edge computing to support gamified physical education in junior high schools enables real-time data processing and interactive, low-latency feedback that overcome the limitations of traditional, static sports game instruction. In our study, 496 students completed questionnaires, and 45 classes participated in a controlled experiment comparing edge-empowered gamified lessons to conventional methods. The results showed a 38% faster class assembly time (2.5 vs. 4 minutes) and an average PE score improvement of over two points, with higher rates of excellence (approximately 50% vs. 36%) and passing (96% vs. 92%). These findings confirm that integrating edge computing into sports games diversifies teaching strategies, enhances student engagement, and improves physical performance.